(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This project discussed about the performance analysis of Load Frequency Control (LFC) of single-area nuclear power systems. The LFC is achieved by the support of a Proportional Integral Derivative (PID) controller as implemented as a secondary controller. The controller gain values are tuned by the conventional tuning method (trial and error). During unexpected power demand occurs in the power system, the frequency in the system is oscillated from the standard limit. The PID controller helps to control the oscillation and bring back the frequency to standard. The gain values are tuned with different cost functions (Integral Absolute Error (IAE), Integral Time Absolute Error (ITAE) and Integral Square Error (ISE). The conventional – PID controller provides better time domain specification.